Inhibition of Ca2+-independent phospholipase A2β (iPLA2β) ameliorates islet infiltration and incidence of diabetes in NOD mice - Bone, R. N.; Gai, Y.; Magrioti, V.; Kokotou, M. G.; Ali, T.; Lei, X.; Tse, H. M.; Kokotos, G.; Ramanadham, S. (Diabetes, 2015)
Autoimmune β-cell death leads to type 1 diabetes and with findings that Ca2+-independent phospholipase A2β (iPLA2β) activation contributes to β-cell death, we assessed the effects of iPLA2β inhibition on diabetes development. Administration of FKGK18, a reversible iPLA2β inhibitor, to non-obese diabetic (NOD) mice significantly reduced diabetes incidence in association with (a) reduced insulitis, reflected by reductions in CD4+ T-cells and B-cells, (b) improved glucose homeostasis, (c) higher circulating insulin, and (d) β-cell preservation. Further, FKGK18 inhibited production of TNFα from CD4+ T-cells and antibodies from B-cells, suggesting modulation of immune cell responses by iPLA2β-derived products. Consistent with this, (a) adoptive transfer of diabetes by CD4+ T-cells to immunodeficient and diabetes-resistant NOD.scid mice was mitigated by FKGK18 pretreatment and (b) TNFα production from CD4+ T-cells was reduced by inhibitors of cyclooxygenase and 12-lipooxygenase, which metabolize arachidonic acid to generate bioactive inflammatory eicosanoids. However, adoptive transfer of diabetes was not prevented when mice were administered FKGK18-pretreated T-cells or FKGK18 administration is initiated with T-cell transfer. Our observations suggest that iPLA2β-derived lipid signals modulate immune cell responses, raising the possibility that early inhibition of iPLA2β may be beneficial in ameliorating autoimmune destruction of β-cells and mitigating type 1 diabetes development.